Entrepreneurial logistics: an application of timmons model in the mini business project for undergraduate business students - Sapto J. Poerwowidagdo; Wee Yu Ghee (2011)
The students of the Faculty of Entrepreneurship and Business, Universiti Malaysia Kelantan pursued a subject called Trade Logistics and Distribution. As part of the course assessment, students were divided into groups and each group was required to implement a mini business project in entrepreneurial logistics. They were free to work on any kind of business along the logistics chain, ranging from suppliers, distributors, manufacturers, wholesalers, retailers to consumers. This paper aimed to trace the application of Timmons model implementation. Finding show that students perceived resource availability as highly important in ensuring the success of the entrepreneurial project, and this is followed by the need for creativity and leadership quality. Correlation analysis indicates that creativity is significantly related to leadership quality, teamwork, resources available and opportunity identified. Leadership quality was also found to have influence on resource availability. Therefore, this study proves the relevancy of Timmons Model of the Entrepreneurial Process which dictates that the key to any business success lies with the entrepreneur.